Causation between Consumption, Export, Import, and Economic Growth of Oman - Uzma Khan; Aarif Mohammad Khan; Md. Shabbir Alam; Nouf Alkatheery (ETIKONOMI, 2022)
To examine the causation between consumption, export, import, and economic growth for the Sultanate of Oman using yearly time series data collected from the World Bank for 2000-2018. Further, it was tested by basic statistics, the Bound test with the ARDL model, and the Granger-causality tests. The findings of the Bound test analysis indicate the presence of both long-run and short-run associations among competing variables. The ARDL Model result reflects that imports have both short-run and long-run effects, supported by the Granger Causality tests by indicating the presence of unidirectional causality import to economic growth and import to consumption. The outcome of the study revealed that import is essential for economic growth as imports can absorb foreign technology in the domestic economy that can boost the export and further act as an engine of growth. How to Cite:Khan, U., Khan, A. M., Alam, M. D., & Alkatheery,N. (2022). Causation Between Consumption, Export, Import & Economic Growth of Oman. Etikonomi, 21(1), 67-78. https://doi.org/10.15408/etk.v21i1.20034.